2017
DOI: 10.7196/samj.2017.v107i3.12111
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance patterns and beta-lactamase identification in Escherichia coli isolated from young children in rural Limpopo Province, South Africa: The MAL-ED cohort

Abstract: Background. Antibiotic resistance is a growing problem worldwide. Mechanisms of resistance vary, and some can confer resistance to multiple classes of antibiotics. Objective. To characterise the antibiotic resistance profiles of Escherichia coli isolates obtained from stool samples of young rural children exposed or unexposed to antibiotics. Methodology. The samples were collected from children aged 4 -12 months who were participants in the Etiology, Risk Factors, and Interactions of Enteric Infections and Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In the present study, large proportions of the isolates originating from various sources displayed significant susceptibilities to the aminoglycoside; amikacin and the carbapenem; meropenem. A similar outcome of no resistance against imipenem and two aminoglycosides was obtained in a previous study among young children in the Limpopo Province of South Africa [69]. These findings are of great therapeutic significance particularly because carbapenems especially meropenem are often used as the first-line antibacterial agents for infections caused by AmpC beta-lactamase-producing Enterobacteriaceae.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, large proportions of the isolates originating from various sources displayed significant susceptibilities to the aminoglycoside; amikacin and the carbapenem; meropenem. A similar outcome of no resistance against imipenem and two aminoglycosides was obtained in a previous study among young children in the Limpopo Province of South Africa [69]. These findings are of great therapeutic significance particularly because carbapenems especially meropenem are often used as the first-line antibacterial agents for infections caused by AmpC beta-lactamase-producing Enterobacteriaceae.…”
Section: Plos Onesupporting
confidence: 83%
“…Although the CTX-M enzymes in ESBL producers are the most frequently detected globally [78], the TEM type enzymes are known to be horizontally transferrable with ease and are degraded by clavulanic acid [78,79]. The significant number of ESBL producing isolates positive for the bla TEM gene, do not agree with previous studies by Oduro-Mensah et al [80] and Bajai et al [81] who reported lower frequencies of detection; 41.8% and 48.7% respectively although comparable to a very high occurrence rate (95.1%) in penicillin-resistant E. coli isolated from young children in the Limpopo province of South Africa [69]. It is worth mentioning that ESBL producers are clinically significant because associated infections are related to high mortality, lengthened hospital stay, failure of therapy and general health cost.…”
Section: Plos Onementioning
confidence: 63%
“…Penicillin’s (ampicillin, amoxicillin and clavulanic acid) and cephalosporins (cefotaxime) are the main β - lactam antibiotics used for veterinary and human medicine ( Defrancesco et al, 2017 ; Pazda et al, 2019 ). The instability of the β - lactam ring and its susceptibility to hydrolysis makes β - lactam antibiotics, especially penicillin, not easily detected in WWTPs ( Pazda et al, 2019 ).…”
Section: Arbs and Args In Wwtpsmentioning
confidence: 99%
“…This may be because clinical E. coli isolates frequently co-carry multiple ESBL genes with varying hydrolysis spectra to different antibiotics, leading to treatment failure ( Seyedjavadi et al, 2016 ; Gumede et al, 2021 ). The genes that confer resistances to ESBL is the bla CTX-M ( Bockelmann et al, 2009 ; Defrancesco et al, 2017 ), while the bla TEM and bla SHV genes confer resistance to the narrow-spectrum β-lactams ( Defrancesco et al, 2017 ). Specific variants of these, such as bla SHV-5 , have the ability to hydrolyze broad-spectrum cephalosporins and monobactams ( Nzima et al, 2020 ).…”
Section: Arbs and Args In Wwtpsmentioning
confidence: 99%
“…MAL-ED is a multicountry, prospective, observational birth cohort study carried out to improve understanding of the interactions of enteric infections, childhood illnesses, vaccine responses, environmental enteropathy, physical growth and cognitive development. [7] In this edition of the SAMJ, DeFrancesco et al [8] demonstrate that strains of Escherichia coli, a common cause of bacterial gastroenteritis, produce extended-spectrum beta-lactamase (ESBL). The production of ESBL allows bacteria to thrive in the presence of therapeutic doses of several clinically important antibiotics, potentially complicating management.…”
Section: Guest Editorialmentioning
confidence: 99%